The University of the Philippines Filipinana Dance Group in concert [videorecording] Kayumanggi at iba pa, held at the University Theater on February 23, 1993. (U.P. Filipiniana Dance Group, 1993)
A dance presentation of the U.P. Filipiniana Dance Group.